2018
DOI: 10.1016/j.jcs.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural changes to proso millet protein bodies upon cooking and digestion

Abstract: Cooking results in a drastic decline in digestibility of proso millet proteins, panicins. Scanning electron and confocal microscopy were used to observe morphological changes in proso millet protein bodies upon cooking and digestion that could be associated with the loss in digestibility. Spherical protein bodies (1-2.5 mm) were observed in proso millet flour and extracted protein. Cooking did not result in any noticeable change in the size or shape of the protein bodies. However, upon digestion with pepsin th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…This data corroborate with the particle size distribution Figure 2. It can also be observed from the scanning electron microscopy (SEM) images that there were indentations on the surface of the larger starch granules which have been previously reported as a characteristic of the starches from Panicoideae subfamily to which proso millet belong (Fannon & Bemiller, 1992; Gulati et al, 2018). These indentations are the places where the smaller protein and starch granules were previously installed.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…This data corroborate with the particle size distribution Figure 2. It can also be observed from the scanning electron microscopy (SEM) images that there were indentations on the surface of the larger starch granules which have been previously reported as a characteristic of the starches from Panicoideae subfamily to which proso millet belong (Fannon & Bemiller, 1992; Gulati et al, 2018). These indentations are the places where the smaller protein and starch granules were previously installed.…”
Section: Resultsmentioning
confidence: 68%
“…All the milled fractions showed some intact endosperm but the original dense structure of proso millet kernel appeared to be broken into irregular fragments with starch being embedded onto protein. Starch granules were polygon in shape and were connected to one another thus resulting in a compound starch granule as in case of rice and oats (Gulati, Zhou, Elowsky, & Rose, 2018). According to Yu et al (2014) there are two distinct sizes of starch granules observed in proso millet flour: (a) A‐type and (b) B‐type with particle size of >9.9 and <9.9 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In order to promote proso millet for human consumption, our previous work focused on evaluation of proso millet protein quality. We found a substantial decline in protein digestibility during thermal processing due to hydrophobic aggregation. , This could prove to be a significant hurdle in promoting the crop as human food.…”
Section: Introductionmentioning
confidence: 81%
“…We found a substantial decline in protein digestibility during thermal processing due to hydrophobic aggregation. 7,8 This could prove to be a significant hurdle in promoting the crop as human food.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Protein digestion is influenced by the other components in food (such as polyphenols or other food matrices ) and processing conditions. The processing can cause very complex reactions between food components, which can result to significant changes in the digestibility of food components.…”
Section: Introductionmentioning
confidence: 99%